Developing A Structural Model of Psychological Factors Affecting Women's Sexual Function - Kazemi Mojarad, Maliheh; Khalatbari, Javad; Moazedian, Ameneh; Sotodeh Asl, Nemat (Applied Family Therapy Journal (AFTJ), 2022)
Aim: Several factors have a role in the formation of sexual activity, some of which have been identified in previous studies. In this regard, the aim of this study was to investigate and determine the psychological factors affecting women's sexual function and develop its structural model. Method: The method of this study is correlation (structural equation modelling). From the study population, which included all Iranian women present in cyberspace in 2020, 386 people were selected using available sampling method. Amos software was used to analyze the research data to present the model. Results: The findings of the present study showed that sexual knowledge, sexual attitude, sexual self-efficacy and sexual self-efficacy had indirect effect on sexual function through sexual redress (P